2020
DOI: 10.1089/jmf.2019.0069
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hypoglycemic Effect of Pomegranate Juice and Its Mechanism of Action: A Systematic Review

Abstract: Pomegranate juice (PJ) has gained popularity attributed to its phenolic compounds and their medicinal properties. Its potential hypoglycemic effect has been related to enzymatic inhibition, insulin release, and the protection of pancreatic tissue. These effects depend on several aspects, such as the content and composition of phenols in pomegranate and characteristics of the organism that consumes the juice. The objective of this study was to systematically review scientific evidence investigating the hypoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
(171 reference statements)
0
7
0
1
Order By: Relevance
“…A 2020 systematic review on the hypoglycemic effect of pomegranate by Virgen-Carrillo et al [300] revealed that the evidence's methodology is heterogeneous, including study design and intervention characteristics. The studies' patients varied widely in clinical features: healthy, obese, diabetic people, metabolic syndrome, cardiovascular pathologies, and women with polycystic ovarian syndrome [300].…”
Section: Insulin Resistance and Diabetesmentioning
confidence: 99%
“…A 2020 systematic review on the hypoglycemic effect of pomegranate by Virgen-Carrillo et al [300] revealed that the evidence's methodology is heterogeneous, including study design and intervention characteristics. The studies' patients varied widely in clinical features: healthy, obese, diabetic people, metabolic syndrome, cardiovascular pathologies, and women with polycystic ovarian syndrome [300].…”
Section: Insulin Resistance and Diabetesmentioning
confidence: 99%
“…It could be affected by monosaccharide composition, molecular weight, branched chain structure, high-level structure, etc. Existing studies have found that the mechanisms of polysaccharides for hypoglycemic activity mainly include regulation of enzyme activity, liver glucose metabolism, intestinal flora, protection and reparation of pancreatic islet cells, and improvement of insulin sensitivity [ 105 , 106 , 107 , 108 , 109 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…α-Amylase and α-glucosidase are enzymes that promote the breaking of α-1,4-glycosidic bonds in starch, maltose, sucrose and oligosaccharides and hydrolyze them into monosaccharide that are easy to digest and be absorbed by the human body, such as glucose [ 106 ]. This caused the postprandial blood glucose levels of diabetic patients to increase and insulin sensitivity to be reduced, even lead them to serious complications and aggravate the condition [ 110 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…The work suggested that pome granate juice polyphenols could reduce the postprandial glycemic response of bread. Ad ditionally, punicalagin was an effective in vitro inhibitor of human α-amylase to the drug acarbose, a drug which acts by inhibiting human α-amylase [54,55], while ellagic acid and punicalin were less effective [14].…”
Section: Human Studiesmentioning
confidence: 99%
“…Pomegranate polyphenols like ellagic acid and punicalagin appear to have inhibitory effects on the activity of α-amylase, α-glucosidase, and dipeptidyl peptidase-4 in free-cell systems and adipocyte cell lines. The polyphenols act as α-amylase inhibitors like the drug acarbose [54,55]. Bellesia et al [64] demonstrated that ellagic acid and punicalagin (exclusive to pomegranate) inhibited α-glucosidase [64].…”
Section: In Vitro Studiesmentioning
confidence: 99%